Effect of combined exercise and nutrition on bone density in postmenopausal women-a systematic review and meta-analysis. - liu, Jie; Li, Xun; Zhang, Wenhua; Miao, Tingting; Wang, Xiaoqiang (Nutrition & Metabolism, 2025)
Background: Postmenopausal women are subject to hormonal fluctuations, a rapid decline in bone mineral density (BMD) and a significant increase in fracture risk, and both exercise and nutritional interventions have a positive impact on BMD. The aim of this study was to evaluate the effects of combined exercise and nutrition interventions compared to single nutrition or exercise interventions on BMD in postmenopausal women and specific combined strategies to improve BMD. Methods: A systematic search on PubMed, Embase, Cochrane Library, Web of Science, Google Scholar databases and studies identified until April 4, 2025 were performed following strictly the PRISMA evaluation guidelines.The risk of bias was assessed using the Cochrane Risk of Bias Tool, the quality of evidence was evaluated using the GRADE approach, and data analysis was performed using Stata 17.0. Results: A total of 24 RCTs involving 2,236 postmenopausal women were included. Meta-analysis results showed that EN vs. N demonstrated a positive effect on BMD at the femoral neck (SMD = 0.17, 95% CI: 0.07–0.27, p = 0.0006), lumbar spine (SMD = 0.20, 95% CI: 0.07–0.33, p = 0.003), and total hip (SMD = 0.16, 95% CI: 0.03–0.28, p = 0.014). However, no statistically significant difference in BMD at the same anatomical site was observed EN vs. N. The robustness of the results of subgroup analysis is limited due to differences in intervention regimens, study populations, and sample sizes across different studies. Conclusions: Based on current evidence, there is insufficient support for universal evidence-based recommendations regarding specific combined intervention strategies. Trial registration/protocol registration: PROSPERO (CRD420251053527).